The Effective Use of Coal Combustion Products (CCPs) in Ashphalt Pavements - (:unkn) unknown (My University, 2016)
Hot-Mix Asphalt (HMA) is one of the most widely used construction materials. The National Asphalt Paving Association (NAPA) estimated that there are over 2.6 million miles of roadway surfaces paved in the United States and 94% of these roads are paved with asphalt. NAPA also estimates that approximately 550 million tons of asphalt worth over $30 billion a year is produced in the United States. At such a huge production rate, innovative solutions need to be developed so that asphalt pavements last longer and can also reduce the production and maintenance costs. Producing sustainable asphalt materials can provide for improved infrastructure which is required for the operational needs of society. Coal Combustion Products (CCPs), such as fly ash materials, are by-products of the coal combustion process. Fly ash is one of the most commonly used by-product pozzolan. These materials are unique in that they have a spherical shape and the small spherical particles can improve the workability and reduce the porosity when mixed with other binding materials. In 2006, the American Coal Ash Association (ACAA) reported that there has been 72.4 million tons of coal ash produced in which only about 52,608 tons of fly ash was used as mineral fillers in asphalt applications. Since 2006, there has been no data on the use of fly ash in asphalt applications. Researchers have found beneficial uses of fly ash in asphalt mastics and asphalt pavements. However, this research has been limited to older testing procedures and only few researchers have reported on the effects of CCPs in asphalt using Superpave® protocol. By further systematic investigation of the effect of CCPs in asphalt, better conclusions can be made regarding the potential favorable effects of CCPs in asphalt. This research investigated the effects of CCPs in asphalt mixtures in terms of asphalt film thickness, workability, aging resistance, moisture damage resistance, intermediate-temperature fatigue cracking resistance, and low-temperature thermal cracking resistance. Control mixtures (5.5% binder content) were compared to ASHphalt mixtures with a 10% (by mass) binder replacement with CCP. The CCPs used were a WE05 (Class C), TA11 (Class F), LG14 (Class F), and SF15 (SDA – Spray Dryer Absorber material). For the Control and ASHphalt mixtures, it was verified that no major differences were observed or recorded for aggregate coating quality or mixing performance. Compaction efforts were reduced for ASHphalt mixtures (compacted at 145oC) as compared to the Control mixtures (compacted at 140oC). The minor increase in compaction temperature was negligible but was necessary to reduce the material viscosity so that compaction efforts were more comparable to the Control mixtures. The addition of CCPs resulted in an enhanced aging resistance for mixtures with LG14 (F) and SF15 (SDA). Indirect Tensile Testing (IDT) proved that the ASHphalt mixtures developed higher strengths than the Control mixtures, especially for WE05 (C) and TA11 (F) mixtures. Moisture damage resistance was evaluating using Tensile Strength Ratio (TSR) and it was discovered that all ASHphalt samples, especially LG14 (F), developed a better TSR than the Control samples. Fatigue testing was performed at intermediate temperatures (20 ± 1oC) to evaluate the number of cycles each sample could withstand before a drop in E* (Complex Modulus). Every ASHphalt material performed better than the Control mixtures for fatigue testing, especially TA11 (F) mixtures as this material withstood 149,250 cycles before failure with a vertical deformation rate of 6.52E-06 mm/cycle. Thermal cracking resistance was evaluated at low temperatures (-18 ± 1oC) by using the Semi-Circular Bending (SCB) test. For Fracture Energy (Gf) all ASHphalt mixtures performed better than the Control mixture, specifically LG14 (F) as this mixture performed the best. For Fracture Toughness (KIC), only LG14 (F) performed better than the Control mixture. Lastly, all mixtures demonstrated lower Stiffness (S) values, especially TA11 (F), than the Control mixture and this was desirable.
Keywords: Coal Combustion Products; Fly Ash; Hot Mix Asphalt; Pavements